2011
DOI: 10.1038/nature09819
|View full text |Cite
|
Sign up to set email alerts
|

A long noncoding RNA maintains active chromatin to coordinate homeotic gene expression

Abstract: The genome is extensively transcribed into long intergenic noncoding RNAs (lincRNAs), many of which are implicated in gene silencing1,2. Potential roles of lincRNAs in gene activation are much less understood3,4,5. Development and homeostasis require coordinate regulation of neighboring genes through a process termed locus control6. Some locus control elements and enhancers transcribe lincRNAs7,8,9,10, hinting at possible roles in long range control. In vertebrates, 39 Hox genes, encoding homeodomain transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,670
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,808 publications
(1,749 citation statements)
references
References 46 publications
42
1,670
1
8
Order By: Relevance
“…4A). Previous studies have shown that the HOX gene clusters (HOXA, HOXB, HOXC, and HOXD) are well conserved across species and several lncRNAs have been shown to be functionally important within these regions (1,12,13).…”
Section: Profile Of Lncrna Expression In Tgf␤-induced Emt Inmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Previous studies have shown that the HOX gene clusters (HOXA, HOXB, HOXC, and HOXD) are well conserved across species and several lncRNAs have been shown to be functionally important within these regions (1,12,13).…”
Section: Profile Of Lncrna Expression In Tgf␤-induced Emt Inmentioning
confidence: 99%
“…Expression of LncRNA-HIT Is Conserved and Is Elevated in Human Invasive Ductal Breast Cancer-LncRNA-HIT resides in the 5Ј distal Hoxa gene cluster, a region of the genome that is highly conserved (12,22). We therefore used BLAST analysis software to evaluate the conservation of lncRNA-HIT in humans and the potential for orthologs residing in the same genomic location.…”
Section: Lncrna-hit Is Up-regulated In 4t1 Cells and Its Depletion Inmentioning
confidence: 99%
“…Les lncRNA peuvent potentiellement lier l'ADN, des protéines ou d'autres ARN, formant des plateformes d'échafaudage et permettant ainsi l'interaction entre diverses molécules fonctionnelles (Figure 4). Certains lncRNA peuvent modifier le contexte chromatinien près de leurs gènes cibles, en recrutant des facteurs de transcription ou des acteurs de la modification d'histones ou de la réorganisation de la chromatine, favorisant ou réprimant ainsi la transcription de gènes cibles, selon le [20,21]. Les lncRNA sont aussi largement impliqués dans les processus post-transcriptionnels liés à la biogenèse des ARNm, tels que l'épissage, le transport, la traduction et la dégradation des ARNm (Figure 4).…”
Section: Fonctions Des Lncrna Dans Les Processus Physiologiquesunclassified
“…In particular, DBE-T interacts with one of the Trx components, the ASH1L protein, which has also been studied in Drosophila, demonstrating its involvement in the activation of Hox gene expression when it is recruited to Hox regulatory elements by lncRNAs [9]. Wang et al [10] described the first activatory lncRNA in 2011: HOTTIP, a long intergenic non-coding RNA (lincRNA) involved in the production of HOXA genes. Cabianca et al [1] have identified the first lncRNA linked to the Trithorax activation complex in relation to a particular disorder.…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd) Is a Neuromuscmentioning
confidence: 99%